Model Penguatan Kapasitas Usaha Perempuan Berbasis Koperasi melalui Hilirisasi Komoditas Kentang - Nurliana Nurliana; Muhammad Ansar Anto; Ika Wisudawaty; Sri Hutami Adiningsih S; Puji Novita Sari (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Women’s economic empowerment based on local potential represents a strategic approach to strengthening community economic self-reliance. However, members of the Tonasa Sukses Mandiri Cooperative in Tombolo Pao District, Gowa Regency, continue to face various challenges in developing potato-based enterprises. Potatoes are generally marketed as fresh produce, resulting in limited value addition, while cooperative members also face constraints related to processing skills, packaging, business management, and digital marketing. This community engagement program aimed to strengthen women’s entrepreneurial capacity by promoting the downstream processing of potatoes into value-added products. The program employed a Participatory Rural Appraisal (PRA) approach, comprising the identification of local potential and key challenges, participatory program planning, program implementation, and participatory monitoring and evaluation. The program was implemented through training in potato chip production, the application of appropriate simple technologies, assistance with packaging and branding, business management training, and digital marketing. The results demonstrated improvements in participants’ knowledge and skills in processing potatoes into value-added products, applying simple technologies to enhance production efficiency, developing product packaging and brand identity, maintaining basic financial records, and utilizing digital media for marketing purposes. The program contributed to strengthening the entrepreneurial capacity of women within a cooperative-based framework and to sustainably increasing the added value of potato commodities.